2x+6
The answer is -32 Sum of -16+8 = -8 Half of -8 = -4 Sum of -5+9 = 4 Twice of 4 = 8 Product = 8*(-4) = -32
2(k+4)
It is 2*(x+4)
6 - 4 = 2.
2x+6
If the sum of a number and 4 is (X + 4) then twice that is 2(X + 4) which is 2X + 8
2(n + 4) < !2 n + 4 < 6 n < 2
x+4.
The answer is -32 Sum of -16+8 = -8 Half of -8 = -4 Sum of -5+9 = 4 Twice of 4 = 8 Product = 8*(-4) = -32
2(k+4)
Three times the difference of a and m divided by twice their sum is equal to 6(a squared - m squared). 3(a - m)/2(a + m)
To calculate 4 times the sum of a number and 6, you would first find the sum of the number and 6, then multiply that sum by 4. Let's represent the number as 'x'. So, the sum of the number and 6 would be x + 6. Multiplying this sum by 4 gives you the expression 4(x + 6), which simplifies to 4x + 24.
The sum of the numbers 8, 6, and 4, is 8 + 6 + 4 = 18.
18 and 6
The sum of 10 plus -6 is equal to 4. The equation would read 10+-6=4.
It is 2*(x+4)